Central banking in the aftermath of the global economic crisis - Anita Angelovska Bezhoska (National Bank of the Republic of Macedonia, 2019)
The worldwide financial crisis revealed that some of the basic consensuses concerning the macroeconomic policy framework and the roles of the central banks were no longer tenable. This prompted rethinking of central bank objectives, strategies and policy instruments, with particular focus on the interactions between monetary and financial stability policies. This paper sheds some light on the flaws exposed during the crisis, debates within the academia and policy-making community and new evolving thinking about the roles and responsibilities of the central banks. The paper also reflects on the crisis' bearing on the roles and responsibilities of the National Bank of the Republic of North Macedonia. In the last decade, legal framework and operational practices were amended to strengthen financial stability mandate and macro prudential policy toolkit of the central bank, to enhance financial stability coordination among regulatory agencies, as well as to improve micro prudential supervision. To support monetary and financial policy decision making, statistical framework was significantly upgraded. Furthermore, given the importance for preserving financial stability, a focus was placed on financial education and consumer protection.
Keywords: E42; E58; 330; central bank; crisis; monetary policy; fiscal policy; macro prudential mandate